Diversity of Order Lepidoptera at Different Levels of Canopy Covers Around Panten Camping Ground, Mount Ciremai National Park - Fariha, Ria Raudhatul; Ramadhania, Laila; Fahmawati, Putri Dewi; Supriyadi, Supriyadi; Nufus, Malihatun (Jurnal Ilmu Kehutanan, 2025)
Mount National Ciremai Park has abundant biodiversity, including the insect order Lepidoptera. Therefore, this research aimed to determine the diversity of order Lepidoptera based on different levels of canopy cover around Panten Camping Ground, Mount Ciremai National Park. This research used an exploration survey using a 100 m transect line and three observation transect lines with different levels of canopy cover. Based on the result of observation, 225 individual Lepidoptera were identified from 26 species and 8 families. The diversity of Lepidoptera showed that 4, 5, and 7 families were at the open, moderate, and closed canopy covers, respectively. Open canopy areas had the most significant number of species, namely 18. In addition, the most commonly found species was Bradina diagonalis, with 82 individuals. The diversity index value (H') of the order Lepidoptera around Panten Camping Ground was recorded at 1.62, 2.14, and 2.08 in open, medium, and closed canopy areas, respectively. The diversity index results showed that the levels of canopy cover did not affect insect diversity, while temperature, humidity, plant species, and springs had a significant influence.